Energy Storage Options for Hybrid Diesel Electric Shunting Locomotives - Wolfs, Peter (University of Tasmania, 2005)
Shunting locomotives are required to produce high powers during shunting operations but may be idle for many hours each day. A key issue with a hybrid conversion is battery life. Shunting locomotives are required to develop typically 1000hp to 2000hp for periods of perhaps a few minutes and the battery is sized for its capacity to deliver instantaneous power. This paper will examine typical shunting duty cycles for a 1000 hp case study where a 520Ah 880V battery is applied. Methods of estimating battery life based on amp-hours exchanged with correction factors for time duration and peak currents are explored. Alternate storage devices such as ultra capacitors can provide methods of significantly reducing the peak battery discharge current and could potentially halve the battery mass.